2014
DOI: 10.1177/0011000014557499
|View full text |Cite
|
Sign up to set email alerts
|

International Education and Service Learning

Abstract: The field of counseling psychology continues to see a perpetual underutilization of mental health resources by many cultural groups, including international populations. Underutilization of services is due, in part, to psychologists' deficiency in cultural and international competency. International education-an experiential learning technique that involves cultural contact-has been proposed as an alternative method for training students to work effectively cross-culturally. The current article examines the ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(6 citation statements)
references
References 53 publications
(103 reference statements)
0
6
0
Order By: Relevance
“…In a review of the literature, we sought to identify articles focused on international social justice issues. Regarding our own flagship journals-Journal of Counseling Psychology (JCP) and TCP-we identified one article in JCP (i.e., Chen et al, 2015) and five in TCP (i.e., Bartholomew, Gundel, & Kantamneni, 2015;Koch, Ross, Wendell, & Aleksandrova-Howell, 2014;Sloan, 2005;Smith, Jennings, & Lakhan, 2014;Yoon, Lee, Koo, & Yoo, 2010) in the last 20 years (1996-2015) that directly examined international social justice issues or training activities designed to enhance international social justice competency. When expanding our search to all APA journals, we identified six additional articles (i.e., Bartholomew, 2012;Graziano, 2004;Horne, 1999;Mohamed & Ratele, 2012;Shefer, 2012;Sonn, 2012).…”
Section: Counseling Psychology and International Social Justicementioning
confidence: 99%
See 2 more Smart Citations
“…In a review of the literature, we sought to identify articles focused on international social justice issues. Regarding our own flagship journals-Journal of Counseling Psychology (JCP) and TCP-we identified one article in JCP (i.e., Chen et al, 2015) and five in TCP (i.e., Bartholomew, Gundel, & Kantamneni, 2015;Koch, Ross, Wendell, & Aleksandrova-Howell, 2014;Sloan, 2005;Smith, Jennings, & Lakhan, 2014;Yoon, Lee, Koo, & Yoo, 2010) in the last 20 years (1996-2015) that directly examined international social justice issues or training activities designed to enhance international social justice competency. When expanding our search to all APA journals, we identified six additional articles (i.e., Bartholomew, 2012;Graziano, 2004;Horne, 1999;Mohamed & Ratele, 2012;Shefer, 2012;Sonn, 2012).…”
Section: Counseling Psychology and International Social Justicementioning
confidence: 99%
“…At Oklahoma State University, a service learning course is offered to counseling psychology graduate students which involves traveling to Belize to engage in 10 days of intensive experiences in cultural immersion and social justice activism (Koch et al, 2014). A 4-week study abroad diversity course offered at the University of St. Thomas aims to enhance students' cross-cultural competency by engaging in intercultural, service learning activities (Smith et al, 2014). The Supervision course at Lehigh University offers opportunities to engage in cyber supervision of trainees in different countries (A. Inman, personal communication, June 23, 2017).…”
Section: Cultivation Of Cross-cultural Sensitivitymentioning
confidence: 99%
See 1 more Smart Citation
“…First, study abroad programs focusing on service learning and international experiential learning techniques have been included in some psychology training programs for many years. While the intent of these learning programs is to increase international competencies among students, it is rare for training programs to include international learning, and few efforts A c c e p t e d M a n u s c r i p t 6 (e.g., Smith, Jennings, & Lakhan, 2014) to collect data on these experiences have been conducted. While these experiences are important they do not offer robust training into international competencies, as that requires more systemic efforts.…”
Section: International Competenciesmentioning
confidence: 99%
“…Similarly, the authors have also argued that a potentially beneficial avenue to increase cultural competency during training is through study abroad experiences (Irwin & Davies, 2020;Smith et al, 2014). Research has overwhelmingly found that intergroup contact can significantly decrease biases towards others and increase knowledge and understanding (Pettigrew et al, 2011).…”
Section: Introduction To Critical Training Issues Part I: Meeting the Needs Of A Diverse Nationmentioning
confidence: 99%